PERANAN DPRD UNTUK MENCAPAI TUJUAN DESENTRALISASI DAN PERSPEKTIF DAERAH TENTANG PELAKSANAAN DESENTRALISASI (THE ROLE OF THE REGIONAL ASSEMBLY IN ACHIEVING THE OBJECTIVE OF DECENTRALIZATION AND REGIONAL PERSPECTIVES IN THE IMPLEMENTATION OF DECENTRALIZATION) - Prof. H. Syahruddin, SE. MA, Werry Darta Taifur (Regional University Research On Decentralizatio, 2002)
In order to strengthen the regional institutions on fiscal decentralization, IRIS presented a series of workshops in collaboration with LPEM - FEUI in Jakarta. The Workshops are followed by a number of research projects done by the participants from different regions in Indonesia. The role of DPRD (Regional Assembly) will be very important, according to our point of view, in the implementation of law 22/1999. Beside that, we also want to know the perspective of Government Officials (GO) including members of DPRD, and NGOs, which consist of non-formal leaders, local business leaders and informed academics, on the new law of decentralization. What is the role of DPRD in the new law? Is there any ability of Regional Council (Assembly) to implement the new law properly? What is the perspective of GO including members of DPRD and NGO on the implementation of the law? These are our research questions that we would like to answer in this study. Available information such as the law, the government regulation, the regional regulation, and the issues currently published in the national and local newspaper is used to answer the first and the second research question. Primary data from 51 respondents of non-formal leaders, local business leaders and in formed academics in West Sumatra Province and six regions (Kabupaten and Kota) in West Sumatra is used to know the perspective of GO and NGO. These regions are called as sample areas.